2010
DOI: 10.1002/mds.23346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical subtypes of Parkinson's disease

Abstract: The clinical heterogeneity of Parkinson's disease (PD) may point at the existence of subtypes. Because subtypes likely reflect distinct underlying etiologies, their identification may facilitate future genetic and pharmacotherapeutic studies. Aim of this study was to identify subtypes by a data-driven approach applied to a broad spectrum of motor and nonmotor features of PD. Data of motor and nonmotor PD symptoms were collected in 802 patients in two different European prevalent cohorts. A model-based cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
170
2
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(190 citation statements)
references
References 31 publications
10
170
2
8
Order By: Relevance
“…Several studies indicated that the clinical course and progression of PD are very variable, suggesting the presence of different PD subtypes with a different evolution [26] and [27]. Young age at PD onset has been associated with a slow-progressive disease, with few non-levodopa-responsive symptoms but a higher incidence of motor fluctuations and dyskinesias [28], while a clinical phenotype characterized by the presence of postural instability and gait difficulty (PIGD) seems to be linked to a rapidly-progressive PD course [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that the clinical course and progression of PD are very variable, suggesting the presence of different PD subtypes with a different evolution [26] and [27]. Young age at PD onset has been associated with a slow-progressive disease, with few non-levodopa-responsive symptoms but a higher incidence of motor fluctuations and dyskinesias [28], while a clinical phenotype characterized by the presence of postural instability and gait difficulty (PIGD) seems to be linked to a rapidly-progressive PD course [29].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of clinical heterogeneity has been studied by analyzing subgroups distinguished by age, progression, and clinical symptoms associated with motor patterns, such as dementia, depression, and autonomic symptoms. In a recent European systematic review conducted by van Rooden et al 23 , clinical forms have been grouped into four subtypes categorized by differences in severity of nondopaminergic aspects and motor complications 23 . Characterization of subtypes and the evolution of the disease can define the prognosis and determine therapeutic strategies, creating a growing demand to identify nonmotor clinical aspects of PD such as urinary dysfunction and determine its role as a prognosis factor.…”
Section: Discussionmentioning
confidence: 99%
“…130 A further analysis has suggested that PD sub-types can be largely characterized by the severity of non-dopaminergic features and motor complications and are likely explained by interactions between disease mechanisms, treatment, ageing and gender. 131 Another recent study (PD PROMS group) has looked at the association between motor subtypes and mood. Regression models suggested an increased risk of anxiety in patients with younger age-of-onset and motor fluctuations.…”
Section: Sub-groups In Pdmentioning
confidence: 99%